Disseminating White Male Nationalist Discourses via YouTube: An Analysis of White Power Music Lyrics. Issue 2 (3rd April 2022) - Alexander, Susan M.; Aggarwal, Nicole; Hite, Anastasia M.
ABSTRACT: This study provides a qualitative content analysis of 66 white power songs, uploaded on YouTube between 2013 and 2019, by male musicians from seven countries. Three overarching themes are found in the lyrics: hatred of perceived enemies, justified actions against these enemies, and the adoption of white nationalist values. However, the data also show that the details of these themes vary by time and location. The authors argue that online white power music introduces fluid and contextualized ideologies of white male nationalism rather than repeating a fixed and static ideology. The effect of widely disseminating the various white nationalist ideologies online, as embedded in this cultural product featuring men, will be to normalize a range of offline thoughts and behaviors that were once widely condemned.